X-ray-activated long persistent phosphors featuring strong UVC afterglow emissions. Issue 1 (December 2018) - Yang, Yan-Min; Li, Zhi-Yong; Zhang, Jun-Ying; Lu, Yue; Guo, Shao-Qiang; Zhao, Qing; Wang, Xin; Yong, Zi-Jun; Li, Hong; Ma, Ju-Ping; Kuroiwa, Yoshihiro; Moriyoshi, Chikako; et al.
Abstract Phosphors emitting visible and near-infrared persistent luminescence have been explored extensively owing to their unusual properties and commercial interest in their applications such as glow-in-the-dark paints, optical information storage, and in vivo bioimaging. However, no persistent phosphor that features emissions in the ultraviolet C range (200–280 nm) has been known to exist so far. Here, we demonstrate a strategy for creating a new generation of persistent phosphor that exhibits strong ultraviolet C emission with an initial power density over 10 milliwatts per square meter and an afterglow of more than 2 h. Experimental characterizations coupled with first-principles calculations have revealed that structural defects associated with oxygen introduction-induced anion vacancies in fluoride elpasolite can function as electron traps, which capture and store a large number of electrons triggered by X-ray irradiation. Notably, we show that the ultraviolet C afterglow intensity of the yielded phosphor is sufficiently strong for sterilization. Our discovery of this ultraviolet C afterglow opens up new avenues for research on persistent phosphors, and it offers new perspectives on their applications in terms of sterilization, disinfection, drug release, cancer treatment, anti-counterfeiting, and beyond. Phosphors: Persistent luminescence of UVC light A new category of the luminescent compounds called phosphors displays strong and persistent emission of UVC light, with potential applications including disinfection, drug-release, cancer treatment, and anti-counterfeiting measures. Researchers in China and Japan, led by Hong-Tao Sun at Soochow University in China, created several examples of the new generation of phosphors, which are stimulated into luminescence by X-ray irradiation. The bright UVC emission persists for more than two hours. Theoretical and experimental results suggest generally applicable structural explanations for the luminescent properties. The researchers believe this is the first discovery of persistent phosphors luminescing in the germicidal UVC range. The emitted light is sufficiently strong for sterilization applications. The ability to further stimulate the phosphors with near-infrared light, which can pass through biological tissues, suggests potential for treating cancer or triggering drug release.